Operative procedures in plastic, aesthetic and reconstructive surgery - Hoschander, Ari S.; Salgado, Christopher J. (Christopher John); Kassira, Wrood; Thaller, Seth R. (CRC Press, Taylor & Francis Group, 2016)
Operative Procedures in Plastic, Aesthetic and Reconstructive Surgery is a comprehensive, step-by-step guide to the most common plastic, aesthetic, and reconstructive procedures. Few resources in the field provide such a detailed description of commonly performed operations in one place. Each chapter presents a well-documented technique for a specific clinical diagnosis. It discusses preoperative markings, intraoperative details, postoperative instructions, and avoidance of complications for each surgical procedure presented. The authors use extensive clinical photographs, drawings, and detail.